Reversible Wide‐Range Tuneable Luminescence of a Dual‐Stimuli‐ Responsive Silver Cluster‐Assembled Material. Issue 11 (13th September 2019) - Ma, Xiao‐Hong; Wang, Jia‐Yin; Guo, Jun‐Jie; Wang, Zhao‐Yang; Zang, Shuang‐Quan
Summary of main observation and conclusion: Silver cluster‐assembled materials (SCAMs) are emerging multi‐functional materials and have attracted great attention recently. In this work, we have prepared a new SCAM of [Ag18 (S t Bu)10 (CF3 COO)2 (PhPO3 )(PhPO3 H)4 (bpy‐NH2 )2 ]∙(PhPO3 H2 ) n (denoted as Ag18 bpy‐NH2 ), by a facile one‐pot method. Ag18 bpy‐NH2 adopts a chain‐like structure made of Ag18 clusters bridged by bipyridyl linkers. Ag18 bpy‐NH2 exhibits reversible luminescent mechanochromism upon mechanical stimulation and solvent treatment. Moreover, it also displays luminescent thermochromism with a linear relationship of the temperature to the intensity ratio of the dual emissions over a wide temperature range of 83 to 303 K. This work might provide new insights into the assembly of multifunctional stimuli‐responsive SCAMs. Abstract : Herein, a novel silver cluster‐assembled material Ag18 bpy‐NH2 was prepared and structurally characterized, which exhibits reversible luminescent mechanochromism and thermochromism.